Can abstract painting elicit emotions? - de la Cuétara San Luis, Isabel; San Luis Costas, Concepción (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2018)
The objective of this research is to verify, by an empirical methodology, the existence of an emotion that we have called aesthetics using for it paintings by Kandinsky. The selection of abstract works as stimuli is determined by the fact that they are the formal elements (shape, colour, lines) what constitutes the composition of the works in which there is no reference evocative, as they have no visual references of the real world. Our results indicate that the stimuli used cause alterations in the psychogalvanic response indicates there has been an emotion developed in line with the proposals by James.